Treating drinkers and drug users in the community - Waller, T. A. N.; Rumball, Daphne; Wiley InterScience (Online service) (Oxford, UK ; Malden, MA : Blackwell Science, 2004)
'Treating Drinkers and Drug Users in the Community is the second book in a new collection from Addiction Press. Addiction Press was set up with the express purpose of communicating current ideas and evidence in this expanding field, not only to researchers and practising health professionals, but also to policy makers, students and interested non-specialists. These publications are designed to address the significant challenges that addiction presents to modern society.''The drugs field has undergone a phase of rapid change in recent years and all the nonmedical treatment interventions for those with alcohol problems and dependence can be equally helpful for drug users. This has opened the way for unification of alcohol and drug treatments services as a clinical level, with potential for more efficient service provision and for effective interventions which can be readily adopted in a wide range of settings. Modern drug and alcohol services and all professionals working with substance users will benefit from the initiatives and procedures discussed in this book.'--Jacket.
Theoretical considerations -- Treating drinkers and drug users in the community: an overview -- The political dimension -- Different national approaches -- Prevention and treatment not separate issues but part of a continuum -- Prevention and treatment services for young people -- Prevention and treatment services for adults -- Assessment -- Treatment -- The therapeutic framework -- Understanding behavioural and cognitive-behavioural treatment approaches -- Effective counselling for ongoing client contact -- The nature and timing of care plan interventions -- Brief interventions -- Prescribing interventions -- Everyone needs help to prevent relapse -- Reducing environmental harm and increasing social strength -- Reducing psychological harm and increasing psychological strength -- Working with families -- Substance use and mental health -- Physical health issues -- Women parents and children -- Professionally aided self-help, twelve step work and the maintenance of abstinence -- Epilogue.
Includes bibliographical references (pages 409-448) and index.
Print version record.
Keywords: Substance abuse -- Treatment; Community mental health services; Substance-Related Disorders -- therapy; Community Mental Health Services -- organization & administration; Substance-Related Disorders -- prevention & control; Substance-Related Disorders -- psychology; Polytoxicomanie -- Traitement; Santé mentale, Services communautaires de; Electronic books